Enhancing ESG practices in STEAM and engineering education - Veronika Vadimovna Abduazizova; Gulnoza Tashmukhamedova (BIO Web of Conferences)
The push to integrate Social and Governance (ESG) practices into education in Science, Technology, Engineering, Arts and Mathematics (STEAM) and engineering fields has been gaining momentum. This research aims to investigate how improved ESG practices could impact human resource management in STEAM and engineering education. The main goal of this research is to evaluate how sustainable practices affect outcomes and workforce development. By using the Experience Sampling Method (ESM) to gather real-time data, the study collected feedback from teachers and students from institutions. The study also utilized a PANEL dataset to analyze long-term trends and patterns. The results show that incorporating ESG practices into curriculum design and institutional policies significantly boosts student engagement, satisfaction, and overall educational quality. Teachers reported improved teaching experience and increased motivation, while students showed greater awareness of sustainability issues. Additionally, the research points out connections between ESG efforts and improved retention rates in engineering programs. Overall findings indicate that a strong focus on ESG practices not only creates an inclusive educational environment but also equips students for future challenges in a rapidly changing job market. The importance of this study is in how it can help policymakers and schools understand the advantages of incorporating ESG principles, which can lead to creating a fair educational system.